The Asean Way: The Way To Regional Peace? - Susy Tekunan (Jurnal Hubungan Internasional, 2015)
ASEAN is considered as the most successful multilateral organization in the Asia region, especially in maintaining regional security and peace. The majority of the international observers, though, ASEAN has not produced any significance breakthrough and notable impact and thus deemed to be an ineffective regional organization. The key that separates ASEAN with others and allows it to maintain regional peace and co-operation is its unique diplomatic engagement with its member states, known as the ASEAN Way. The most important element of the ASEAN Way is the practice of the principle of non-interference among its member states. ASEAN members practiced this principle since the founding of the organization to ensure state sovereignty that serves as an expression of respect and equal standing for all member countries. This article explores the possibility of ASEAN Way and its practice of internal diplomacy to be applied in other regional or multilateral organizations. The purpose is first to measure and analyse whether the ASEAN Way is an effective practice that benefits the ASEAN members and the Asia region. If the practice is effective, according to the measure and the scope of the paper, the author is interested to observe whether the practice can be applied to other multilateral organizations. This is a qualitative article, the effectiveness of the ASEAN Way will be observed and analysed through the process and the result from conflict resolutions in ASEAN. The source of research comes from a bevy of academic literature on ASEAN and ASEAN Way as well as journalistic paper and articles.